Noise at workplaces in the call center - SMAGOWSKA, Bożena (Archives of Acoustics, 2010)
In the last years the number of new forms of workplaces, such as call centers, increases. It is defined as a workstation where the basic tasks of a worker are carried out with the use of a phone and a computer. According to statistics, about 1.3-4% of workers are employed in call centers in the European countries. The noise is one of the harmful and annoying hazards of call center workstations. The paper presents the noise sources in call center rooms, assessment criteria of noise and results of noise measurements in call center workstations. The results of measurements show that the noise at call center workstations (during the use of handset receiver phone by operators) can be harmful (causing the risk of hearing loss) and annoying, as it makes it difficult to carry out the basic work activities and causes additionally auditory disadvantageous changes in health.